ARUS HUBUNG SINGKAT DIAMANKAN OLEH PENGARUH KECEPATAN PMT - Wahyudin SN; Tasdik Darmana; Wahyu Yuliansyah (Sutet, 2015)
The short circuit is one of the interference in electric power system that is temporary, this should be overcome by protection equipment protection system. A short circuit is an abnormal relationship to a relatively low impedance occurring between two points having different potentials. The low voltage generated by the disturbance results in endangering the service provided by the electrical system. If the voltage remains low for a few seconds, the machines belonging to the consumer will stop and the generators on the system become unstable. The power cut (PMT) should work as quickly as possible. If the overflow relay (OCR) and ground disturbance relay (GFR) coordinate well and quickly provide interference signals the power breaker (PMT) then the damage could be avoided especially where the short-circuited sparks occur.